SYNOVIAL SARCOMA IN CHILDHOOD: CLINICAL AND RADIOLOGICAL FINDINGS - Xu, Deyong; Zhan, Alai; Luan, Hongmei; Feng, Weihua; Sun, Xihe; Yang, Zuwen (Chinese Journal of Cancer Research, 2013)
Objective: To study the clinical characteristics and radiological features of synovlal sarcoma in childhood and its relation to the diagnosis and treatment. Methods: The clinical radiological features of 15 children with synovial sarcoma proved surgically and pathologically were analyzed. Results: In children, the tumor boundaries are poorly defined dee to paucity of fat, and metastasis usually occurs early. Eight patients in this series had bone involvement, including: direct erosion by tumor causing cortical destruction, indirect pressure defect with sharp margin and reactive bone sclerosis and bone destruction of the primary intraosseous synovial sarcoma. Conclusion: The tumor is often misdiagnosed, the final confirmed diagnosis must be made by histological examination with imaging findings. It is emphasized that the patients should be treated with radiotherapy and chemotherapy preoperatively and postoperatively.